2021
DOI: 10.1101/2021.02.13.431008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent, Novel SARS-CoV-2 PLpro Inhibitors Block Viral Replication in Monkey and Human Cell Cultures

Abstract: Antiviral agents blocking SARS-CoV-2 viral replication are desperately needed to complement vaccination to end the COVID-19 pandemic. Viral replication and assembly are entirely dependent on two viral cysteine proteases: 3C-like protease (3CLpro) and the papain-like protease (PLpro). PLpro also has deubiquitinase (DUB) activity, removing ubiquitin (Ub) and Ub-like modifications from host proteins, disrupting the host immune response. 3CLpro is inhibited by many known cysteine protease inhibitors, whereas PLpro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 55 publications
6
81
0
Order By: Relevance
“…In this group, the main direction seems to be focused on the peptide scaffolds [30]. There are also other proposals for nonpeptide, covalent inhibitors, such as ebselen [37], its derivatives [31], and disulfiram [38]. In the case of the peptide inhibitors, the covalent bond is formed with one of the amino acids of the catalytic triad-Cys111.…”
Section: Resultsmentioning
confidence: 99%
“…In this group, the main direction seems to be focused on the peptide scaffolds [30]. There are also other proposals for nonpeptide, covalent inhibitors, such as ebselen [37], its derivatives [31], and disulfiram [38]. In the case of the peptide inhibitors, the covalent bond is formed with one of the amino acids of the catalytic triad-Cys111.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we provide a set of previously published redocked compounds with reported half maximal inhibitory concentration (IC 50 ) values against 3CL pro [ 38 , 73 , 87 , 88 ] and PL pro [ 40 , [89] , [90] , [91] , [92] ] to give the interested reader more detailed view on the docking score vs. dose concentration relation of in vitro tested compounds. Refer to the supplementary materials in respective .xlsx documents, sheets IC 50 _dockings.…”
Section: Discussionmentioning
confidence: 99%
“…10) [100][101][102][103][104] . In a recent HTS study performed by Zhengnan Shen et al, candesartan as an ARB was identi ed as one of a few compounds that showed inhibitory effects against SARS-CoV-2 PLpro, out of about 15,000 screened compounds 105 .…”
Section: Cha-12 As a Multi-target Inhibitormentioning
confidence: 99%
“…Interestingly, in a recent structure-based drug design attempt, extensive SAR evaluations have led to a chalcone-amide isoster bearing a 2-thienyl at position 3 of ring B for producing the strongest derivatives against SARS-CoV-2 PLpro (Fig. 17A, structure H) 105 . The metaand para-uorophenyl substitutions in positions 2 and 3 of the B-ring also existed in the structure of CHA-7 and CHA-177 which were found to have high docking scores in our compound library.…”
Section: Selective Ligands Towards the Sars-cov-2 Plpromentioning
confidence: 99%